Curriculum windows. - Poetter, Thomas S. (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
Curriculum Windows: What Curriculum Theorists of the 1960s Can Teach Us about Schools and Society Today is an effort by students of curriculum studies, along with their professor, to interpret and understand curriculum texts and theorists of the 1960s in contemporary terms. The authors explore how key books/authors from the curriculum field of the 1960s illuminate new possibilities forward for us as scholareducators today: How might the theories, practices, and ideas wrapped up in curriculum texts of the 1960s still resonate with us, allow us to see backward in time and forward in time - all at the same time? How might these figurative windows of insight, thought, ideas, fantasy, and fancy make us think differently about curriculum, teaching, learning, students, education, leadership, and schools? Further, how might they help us see more clearly, even perhaps put us on a path to correct the mistakes and missteps of intervening decades and of today? The chapter authors and editor revisit and interpret several of the most important works of the 1960s by Louise Berman, Jerome Bruner, WEB DuBois, Elliot Eisner, John Goodlad, James Herndon, John Holt, Philip Jackson, Herb Kohl, Robert Mager, A.S. Neill, Philip Phenix, Neil Postman. Joseph Schwab, Hilda Taba, and Sidney Walton.